2022
DOI: 10.1177/13694332221097730
|View full text |Cite
|
Sign up to set email alerts
|

Shear behavior of web-embedded steel-concrete composite beam

Abstract: To optimize conventional composite beam, this paper proposes a new steel-concrete composite beam without top flange, and discusses the shear behavior of this novel web-embedded steel-concrete composite beam (WSCB). Five patterns of embedded shear connectors are proposed, including the shapes of swallow tail, gear, modified gear, circular hole, and steel bar. A shear experiment on ten specimens with the shear span ratio λ = 1.5 were conducted, considering effects of the concrete slab width ( B) and the shear co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…Naito CJ [22] developed a full-scale bridge model and studied its flexural performance; the results showed that the design and manufacturing method satisfied the AASHTO limit state standard [23]. Yuanlong [24] constructed nine external U-shaped steel-concrete composite beams with an embedded web (WUSCB) and investigated the effects of the shear span ratio, concrete wing width, joint spacing and inclination angle, bottom longitudinal bar diameter, stud and stirrup setting, and U-shaped steel web height-to-thickness ratio on its shear performance.…”
Section: Introductionmentioning
confidence: 99%
“…Naito CJ [22] developed a full-scale bridge model and studied its flexural performance; the results showed that the design and manufacturing method satisfied the AASHTO limit state standard [23]. Yuanlong [24] constructed nine external U-shaped steel-concrete composite beams with an embedded web (WUSCB) and investigated the effects of the shear span ratio, concrete wing width, joint spacing and inclination angle, bottom longitudinal bar diameter, stud and stirrup setting, and U-shaped steel web height-to-thickness ratio on its shear performance.…”
Section: Introductionmentioning
confidence: 99%